ANALYSIS OF THE EFFICIENCY OF A 72 VOLT 15 AH LITHIUM ION BATTERY IN A MOTORCYCLE DESIGNED WITH 3 KW OF POWER (Universitas Pendidikan Indonesia, 2025)
The development of electric vehicle technology is rapidly advancing in line withthe increasing demand for environmentally friendly and energy-efficient transportation. This research aims to evaluate the efficiency level of an electric motor designedusing a 72-volt 15 Ah lithium-ion battery with 3 kW of power,with a primary focus on assessing the performance of electric motors in supportingenvironmentally friendly mobility, while also reviewing the extent to whichbattery technology plays a role in improving the effectiveness of the drive system. The testingwas conducted at the Automotive Laboratory of the Indonesia University of Education usingthe Dyno Test BRT 50 LE and LB equipment. Data was collected through measurements ofvoltage, current, and power under both no-load and 60 kg load conditions. The test results showed variations in output power (P_out) and input power(P_in) with an average efficiency of 61.06%. This value reflects thatthe electric motor is able to work stably even though its efficiency varies ineach test condition. This study confirms that lithium-ion battery-based electric motorshave the potential to be an alternative for sustainable transportation, but there needs to be optimization of technology to improveperformance and efficiency in the future. Perkembangan teknologi kendaraan listrik semakin pesat seiring meningkatnya kebutuhan transportasi ramah lingkungan dan efisiensi energi. Penelitian ini bertujuan untuk mengevaluasi tingkat efisiensi motor listrik yang dirancang menggunakan baterai lithium-ion bertegangan 72 Volt 15 Ah dengan daya 3 kW, dengan fokus utama untuk menilai kinerja motor listrik dalam mendukung mobilitas yang ramah lingkungan, sekaligus meninjau sejauh mana teknologi baterai berperan dalam meningkatkan efektivitas sistem penggerak. Pengujian dilakukan di Laboratorium Otomotif Universitas Pendidikan Indonesia dengan menggunakan alat Dyno Test BRT 50 LE dan LB. Data diambil melalui pengukuran tegangan, arus, dan daya baik pada kondisi tanpa beban maupun dengan beban 60 kg. Hasil pengujian menunjukkan variasi daya keluar (P_out) dan daya masuk (P_in) dengan rerata efisiensi sebesar 61,06%. Nilai ini mencerminkan bahwa motor listrik mampu bekerja dengan stabil meskipun efisiensinya bervariasi pada setiap kondisi pengujian. Penelitian ini menegaskan bahwa motor listrik berbasis baterai lithium-ion berpotensi menjadi alternatif transportasi berkelanjutan, namun perlu adanya optimalisasi teknologi untuk meningkatkan kinerja dan efisiensi di masa depan.